Kebijakan Pemerintah Daerah dalam Penyelenggaraan Urusan Pemerintahan Bidang Kesejahteraan Sosial (Suatu Studi Tentang Pemberdayaan Ekonomi Kerakyatan dalam Mengatasi Anak Terlantar di Kota Mataram) - Chairun Nasirin (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
This research focused on how the function of local government enable of neglected children become apart of the social development and how the government model can be suitable the social matters and society comprehensively. Besides, this research also try to find that execution of local government function regarding the optimalized the social development program, especialy the empowerment program for neglected children. Several programs from the government has been doing to empowered the prosperity of social development to enable the neglected children, such as adherence to order the principal of participation or to eficiency the budget planning from the central government to running the social program. This research recommend; (1) require to conduct the function of local government; (2) to optimalized the program, the local government have to arrange the good program regarding the neglected children; (3) the local government need to strenghthen the system of how to solve the social problem, especially the neglected children program and how to minimized them.Keywords : Government, Social Development, Empowerment